Evading Detection during Adolescence: The Role of Criminal Capital and Psychosocial Factors. (23rd February 2021) - Knowles, Alissa; Rowan, Zachary; Frick, Paul J.; Steinberg, Laurence; Cauffman, Elizabeth
Abstract: Many adolescents engage in crime, but not all youth are caught by law enforcement. Previous work highlights the importance of criminal capital, or assets that help individuals evade police detection. Few studies have extended this work to adolescent offender populations or have considered the contribution of psychosocial and contextual factors to arrest avoidance. The current study uses data from a longitudinal study of first-time adolescent offenders to evaluate the contribution of criminal capital, psychosocial and contextual variables in predicting re-arrest. The results from the longitudinal random effect logit models confirm the contribution of established criminal capital variables in predicting arrest but also highlight the role of psychosocial predictors (future expectations and intelligence). Contextual factors such as parenting and neighborhood disorder had no association with the likelihood of re-arrest. These findings highlight several factors that help youth avoid re-arrest, and may exacerbate continued patterns of illegal behavior.